Odpowiedź :
Odpowiedź:
a)
2x+3=15
2x=15-3
2x=12/:2
x=6
b)
5x+13=23
5x=23-13
5x=10/:5
x=2
c)-5x+3=-12
-5x=-12-3
-5x=-15/:(-5)
x=3
d)4x-7=33
4x=33+7
4x=40.:4
x=10
e)-3x+5=17
-3x=17-5
-3x=12/:(-3)
x=-4
f)-x-2=-11
-x=-11+2
-x=-9/:(-1)
x=9
Szczegółowe wyjaśnienie:
Odpowiedź:
Jak poniżej:
Szczegółowe wyjaśnienie:
a)
2x + 3 = 15
2x = 12
x = 6
b)
5x + 13 = 23
5x = 10
x = 2
c)
-5x + 3 = -12
-5x = -15
5x = 15
x = 3
d)
4x - 7 = 33
4x = 40
x = 10
e)
-3x + 5 = 17
-3x = 12
3x = -12
x = -4
f)
-x - 2 = -11
-x = -9
x = 9